Service Quality And Product Innovation On Interest In Buying Suzuki Brand Motorcycles In Kolaka - Desriyanti Banne; Niar Astaginy; Muhamad Stiadi (Transformasi: Journal of Economics and Business Management, 2023)
This research aims to determine: The influence of service quality on interest in purchasing Suzuki brand motorbikes in Kolaka; The influence of product innovation on interest in purchasing Suzuki brand motorbikes in Kolaka. This research uses quantitative methods. Data collection in this research used observation, literature study, and distribution of questionnaires. The population of this research is the Kolaka community. Meanwhile, the research sample consisted of 130 respondents using techniques accidental sampling. Research instrument testing uses validity and reliability tests with SPSS 22.0. The data analysis technique used in this research is Structural Equation Modeling (SEM) based Partial Least Square (PLS) with testing measurement model (outer model), testingmodel structural (inner model) with smart PLS 4.0. Based on the research results, it is known that there is an influence between Service Quality and Purchase Interest And there is an influence between Product Innovation and Purchase Interest.